2011
DOI: 10.1103/physreve.83.031402
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of nanoparticles into heterogeneous structures with gradient material properties

Abstract: We present a mechanism to form self-assembled functional gradient superlattice structures by subjecting binary nanoparticles in an electric field. The interaction among different dipoles leads to the controllable formation of diverse structures, including particle columns with gradient material properties from inside to outside and various hierarchical layered or three-dimensional particle chain networks. We elucidate how permittivity, volume fraction, particle size, and the frequency of the electric field can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It can be seen from Equation (39) as time elapses, the boundary smears out until the concentration gradient vanishes consequently, the broadening of the Gaussian function occurs. Self-assembly of NPS under influence of electromagnetic field with the frequencies in the optical range has been studied by Park et al [53] and as suggested by Slabko et al [54], when NPs are irradiated by the laser radiation, dipole moment is induced which enhances the formation of structural geometry hence forming an agglomeration. In our case, the downward motion of the agglomerates is demonstrated by FITC fluorescence.…”
Section: ) Heat Generationmentioning
confidence: 97%
“…It can be seen from Equation (39) as time elapses, the boundary smears out until the concentration gradient vanishes consequently, the broadening of the Gaussian function occurs. Self-assembly of NPS under influence of electromagnetic field with the frequencies in the optical range has been studied by Park et al [53] and as suggested by Slabko et al [54], when NPs are irradiated by the laser radiation, dipole moment is induced which enhances the formation of structural geometry hence forming an agglomeration. In our case, the downward motion of the agglomerates is demonstrated by FITC fluorescence.…”
Section: ) Heat Generationmentioning
confidence: 97%
“…Note that the modelling of self-assembly processes is widely covered in the modern literature, as it gives a good qualitative and quantitative description of real physical processes and allows obtaining preliminary parameters for carrying out experiments. Thus, a model for describing the self-assembly of CdTe nanoparticles into helical structures due to light-induced charges was presented in [7], and the processes of nanoparticles self-organization under the action of a non-resonant electromagnetic field with frequencies in a wide range were considered in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Another prospective approach implies the modification of potential energy of the particles in the non-resonant electromagnetic field of the light wave due to particle interactions [12]. Self-assembly of nanoparticles under the action of non-resonant electromagnetic field in the wide frequency range was also investigated [13]. When nanoparticles resonantly interact with the electromagnetic field, this interaction gives new opportunities for selective manipulation of nanoparticles [14].…”
Section: Introductionmentioning
confidence: 99%